Alternative Program From Life Cycle Assessments (LCA) in Sugar Cane to Reduce Environmental Impact - Aulia Ulfah Farahdiba; Anis Yusrin Qonita; Nanik Ratni JAR; Aussie Amalia (Nusantara Science and Technology Proceedings, 2021)
The advantage of the LCA method is that it can comprehensively analyze the potential impacts that can occur on the environment. In this study, a study of the LCA of sugar production. In this study, a sugar factory produces an environmental impact on the gate to gate sugar production process (power plant, milling station, purification station, evaporation station, cooking/crystallization station, and spin) using the Eco-Indicator 99 (H) method. The most significant environmental impacts of the sugar production process are respiratory inorganics, land use, and fossil fuels. The cause of the impact of respiratory inorganics occurs due to air emissions such as particulate matter, nitrogen dioxide, and sulfur dioxide from the boiler. The cause of the effects of land use comes from sugarcane land used as raw material for cane cutter units. In comparison, the impact of fossil fuels occurs due to the use of diesel fuel in the sugarcane planting process and natural gas from the fertilizer production process. Alternative improvement programs can be carried out to reduce the environmental impact caused by the sugar factory production process include the procurement of air emission controllers that meet standards and periodic maintenance. Furthermore, reducing diesel fuel and replacing it with environmentally friendly fuels, paying attention to farmers. Related to increasing productivity based on land suitability assessment, reducing the use of chemical fertilizers, and replacing environmentally friendly fertilizers in the sugarcane planting process.